Manajemen Komunikasi Pengurus dengan Anggota dalam Upaya Meningkatkan Partisipasi Anggota Koperasi sebagai Pemilik : Studi Kasus pada Koperasi Konsumen Rumah Sakit Umum Ranca Badak Bandung, Jawa Barat - Yuanita Indriani; Widianti Agustin (LPPM Universitas Koperasi Indonesia, 2025)
Ranca Badak Consumer Cooperativeis (KRB) a functional cooperative operating at Ranca Badak General Hospital, the purpose of establishing KRB is to improve the welfare of its members; KRB has experienced good business development, this is indicated by the benefits provided by KRB to members, both in the form of economic benefits and social benefits, but the development of KRB's business in the last 3 years has decreased; The locus of this research is KRB, qualitative method used to determine the development of KRB, by analyzing the development trend of members who utilize business services, how members comply with repaying loans to KRB, what benefits does KRB provide for members who actively utilize KRB business units and another important thing is how KRB members participate in collecting their own cooperative capital in the form of mandatory savings payments every month, with the right amount and right time and how KRB communicate with the members in this matter; The results shows that member compliance as cooperative customers is described by how members pay mandatory savings to the cooperative every month. The initial stage of implementing KRB communication management by the Management to increase member participation as KRB owners is through setting KRB communication objectives with members related to the payment of mandatory savings by members every month; in this case the Management has a work target that each member pays the mandatory savings in the right amount and right time every month.